Integrating YouTube and TikTok in Task-Based Speaking Instruction: A Classroom Action Research with EFL Undergraduates - Anwar, Saiful; Sueb, Sueb; Pambayun, Rizki Nurfida (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This classroom action research examined the implementation of a task-based instructional sequence that integrated YouTube and TikTok as spoken-output platforms to support EFL learners’ speaking development. Grounded in Task-Based Language Teaching, the study was conducted with 35 undergraduate EFL students over a five-week period. Learners completed a series of short video-based speaking tasks (60–120 seconds) produced and shared via YouTube and TikTok as part of regular classroom instruction. Data were collected through a speaking pre-test and post-test, baseline and ongoing classroom observations, weekly video task submissions, a post-intervention questionnaire, and learners’ reflective notes. Quantitative data from speaking assessments were analysed descriptively, while qualitative data from observations, questionnaires, and reflections were analysed thematically. The findings indicate improvement across key speaking subskills, fluency, pronunciation, vocabulary, grammar, and comprehension use. Observation data and analysis of weekly video tasks further reveal increased learner engagement, greater willingness to speak, and reduced speaking anxiety during task implementation. Learners’ reflections highlight enhanced speaking confidence, increased awareness of speaking development, and generally positive responses to video-based speaking tasks. The study illustrates how short-video production, when systematically embedded within a task-based classroom action research framework, can support both linguistic development and learner engagement in EFL speaking instruction.